Mechanisms and kinetic parameters for the gas-phase reactions of anthracene and pyrene with Cl atoms in the presence of NOx. Issue 21 (10th February 2016) - Dang, Juan; He, Maoxia
Abstract : The mechanisms of the Cl radical-initiated atmospheric oxidation of anthracene (Ant) and pyrene (Pyr) were investigated by using quantum chemistry calculations. Abstract : Due to their global dispersion and toxicity, polycyclic aromatic hydrocarbons (PAHs) in the atmosphere have become a serious environmental concern. Atmospheric reactions of PAHs with Cl atoms are of critical importance in specific areas such as the marine boundary layer and coastal regions. In this study, the mechanisms of the Cl radical-initiated atmospheric oxidation of anthracene (Ant) and pyrene (Pyr) were investigated using quantum chemistry calculations. The rate constants for the crucial elementary reactions were estimated. The oxidation products of the gas-phase reactions of Ant and Pyr with Cl atoms are chloro-Ants, chloro-Pyrs, 2-chloroanthracen-1-one, 1-chloropyren-2-one, 1-chloropyren-3-one, 4-chloropyren-5-one, 1-chloro-2-hydroperoxyanthracene, 2-chloro-1-hydroperoxyanthracene, 1-chloro-2-hydroperoxypyrene, 4-chloro-5-hydroperoxypyrene, epoxides, dialdehydes, 9-nitroanthracene, 1-nitroanthracene and nitropyrenes. 9-Nitroanthracene can be more easily produced by the gas-phase reaction of Ant with Cl atoms than that of Ant with OH radicals. Water plays a vital role in the formation of 9-nitroanthracene, resulting from the reactions with NO2 . This comprehensive mechanistic study is the first one reported for the Cl radical-initiated atmospheric oxidation of PAHs. The calculated overall rate constants for the Cl addition reactions of Ant and Pyr are 5.87 × 10 −12 and 2.81 × 10 −12 cm 3 per molecule per s, respectively, at 298 K and 1 atm.